Efficacy and safety of oral Pentasa (prolonged-release mesalazine) in mild-to-moderate ulcerative colitis: a systematic review and meta-analysis. (2nd November 2021) - Paridaens, Kristine; Fullarton, John R.; Travis, Simon P. L.
Abstract: Background: Pentasa (prolonged-release mesalazine [5-ASA]) has been available for >30 years as an effective treatment for mild-to-moderate ulcerative colitis (UC). A systematic literature review and meta-analysis was undertaken to provide an up-to-date evaluation of oral Pentasa efficacy and safety for induction and maintenance of remission. Methods: Literature searches were conducted in PubMed, Embase and Cochrane databases, from inception to 02 December 2020. Unpublished studies were also sourced. Meta-analyses using a random-effects model and Bayesian inference compared Pentasa (tablets, granules, capsules) against placebo and other 5-ASAs. Results: Twelve studies involving 3674 patients treated with Pentasa were identified. Pentasa 2–4 g/day was superior to placebo at inducing (absolute risk difference [ARD] at 8 weeks 0.14, 95% CI 0.07‒0.21; p  < .001) and maintaining (ARD 6-12 months 0.18, 95% CI 0.04‒0.33; p  < .05) remission (clinical/endoscopic). Against other 5-ASAs, Pentasa had similar efficacy for induction (ARD <0.001, 95% CI −0.05‒0.05) and maintenance (ARD 0.01, 95% CI −0.07‒0.08) treatment using randomized controlled trial data. Upon inclusion of real-world study data, Pentasa was significantly better at maintaining remission compared both to Eudragit-S mesalazine and sulfasalazine (ARD 0.04, 95% CI 0.02‒0.06; p  < .001). Pentasa (1–4 g/day) had similar treatment-related adverse event rates to placebo (ARD 0.02, 95% CI −0.03‒0.06) and Eudragit-L/S mesalazines (2.25-3 vs 2.4-3 g/day, respectively; ARD −0.03, 95% CI −0.12‒0.05), but was better tolerated than sulfasalazine (3 g/day) (ARD 0.07, 95% CI 0.003‒0.14; p  < .05). Conclusion: This study confirms oral Pentasa is efficacious and well-tolerated in treating active UC and maintaining remission. The availability of multiple forms of Pentasa supports physicians' ability to individualize treatment and optimize dosing to improve outcomes.